Mapping the state-of-the-art of the barriers for personalized preventive approaches worldwide: A scoping review of reviews - Nicolò Scarsi; Abdelrahman Taha; Sara Farina; Tommaso Osti; Luigi Russo; Alessandra Maio; Roberta Pastorino; Stefania Boccia (PLoS ONE, 2025)
Introduction The growing prevalence of chronic diseases globally raised the public health need to improve the effectiveness of preventive medicine through the integration of big data, biological biomarkers and omics technologies. The implementation of personalized preventive approaches in real-world settings is constrained by several barriers. This scoping review aimed to map the barriers hindering the adoption of personalized preventive approaches for chronic diseases in health systems. Materials and Methods PubMed, Web of Science, Scopus and gray literature sources were consulted from 2017 to 2024, to collect reviews on personalized preventive approaches implementation’s barriers. Additionally, we conducted a thematic analysis in order to categorize the identified barriers. The review followed Arksey-O’Malley guidelines and PRISMA-ScR checklist, Results 283 barriers were extracted from 37 reviews, and categorized into six main domains, namely “Research” (30 reviews), “Organizational Aspects” (27 reviews), “Healthcare Professionals” (28 reviews), “Ethical, Legal, and Social Issues” (29 reviews), “Public” (24 reviews), and “Financial concerns” (23 reviews). The research domain was characterized by lack of generalizability, clinical efficacy and cost effectiveness evidence. Organizational barriers included operational inefficiencies and unclear implementation frameworks. Healthcare professionals struggle with insufficient personalized prevention literacy. Ethical concerns, data privacy issues, and health inequities represent a burden to deal with for actual translation into practice, as well as the general mistrust of individuals and inadequate financial mechanisms, Conclusions Our findings showed how several factors threaten the progress of many innovations in the field of personalized prevention across different populations and chronic diseases, highlighting the need for further efforts in personalized preventive approaches implementation.